Magnetic resonance imaging catheter stress haemodynamics post-Fontan in hypoplastic left heart syndrome - Pushparajah, Kuberan (Eur Heart J Cardiovasc Imaging, 2016)
AIMS: Exercise limitation is common post-Fontan. Hybrid X-ray and magnetic resonance imaging (XMR) catheterization allows haemodynamic assessment by means of measurement of ventricular volumes and flow in major vessels with simultaneous invasive pressures. We aim to assess haemodynamic response to stress in patients with hypoplastic left heart syndrome (HLHS) post-Fontan. METHODS AND RESULTS: Prospective study of 13 symptomatic children (NHYA 2) with HLHS post-Fontan using XMR catheterization. Three conditions were applied: baseline (Stage 1), dobutamine at 10 µg/kg/min (Stage 2), and dobutamine at 20 µg/kg/min (Stage 3). Seven consecutive patients received inhaled nitric oxide (iNO) at peak stress. Control MRI data were from normal healthy adults. In the HLHS patients, baseline mean pulmonary vascular resistance (PVR) was 1.51 ± 0.59 WU m(2) and aortopulmonary collateral flow was 17.7 ± 13.6% of systemic cardiac output. Mean right ventricular end-diastolic pressure was 6.7 ± 2.5 mmHg which did not rise with stress. Cardiac index (CI) increased at Stage 2 in HLHS (40%) and controls (61%) but continued to increase at Stage 3 only in controls (19%) but not in HLHS. The blunted rise in CI in HLHS was due to a continuing fall in end-diastolic volume throughout stress, with no significant change in PVR or CI at peak stress in response to iNO. CONCLUSION: Cardiac output post-Fontan in HLHS at peak stress is blunted due to a limitation in preload which is not responsive to inhaled pulmonary vasodilators in the setting of normal PVR.